Organizational Model of the Southern Asia Cluster Family Businesses - Gupta, Vipin; Levenburg, Nancy M.; Moore, Lynda L.; Motwani, Jaideep; Schwarz, Thomas V. (The South East Asian Journal of Management, 2007)
Recently, there has been an increased interest in the family business organization. Traditionally, the ideal typical organizational model was one where the management, governance, and ownership entities are kept separate. This principal agent model has been a subject of public debate in the wake of several corporate scandals. In the family business organization, significant management, governance and ownership is often with the members of a family & its trusted partners. It is common in the US to regulate the management, governance, and ownership roles of the family members by using competitive criteria for the involvement of different members. In Southern Asia cluster (Gupta & Hanges, 2004), on the other hand, it is quite common for the family involvement to be holistic and undivided, where the family collectively owns the shares in the family business. In this work, this organizational model of the Southern Asian family businesses is investigated.